Secrets and disclosure in donor conception. Issue 1 (16th November 2017) - Frith, Lucy; Blyth, Eric; Crawshaw, Marilyn; van den Akker, Olga
Abstract: This article considers the disclosure, sharing and exchange of information on being donor conceived within families, drawing on data from a study undertaken with donor‐conceived adults registered with UK Donor Link (a voluntary DNA‐linking register). This paper considers the narratives of how respondents found out they were donor‐conceived and what events triggered disclosure of this information. This paper then goes on to examine the role secrecy played in their family life and uses the concept of 'display' to explore how secrecy affected their relationships with their immediate and extended family. Secrets are notoriously 'leaky' and we found complex patterns of knowing and uncertainty about whom in the family knew that the person was donor‐conceived. We argue that what is kept secret and from whom provides insights into the multifaceted web of social relationships that can be created by donor‐conception, and how knowledge can be managed and controlled in attempts to display and maintain family narratives of biogenetic connection.